Embracing Diverse Learners: Making Higher Education Inclusive and Effective - Muhammad Shahid Shamim (Journal of the Pakistan Medical Association, 2025)
graduates who can excel in real-world settings.Traditionally, academic success has been viewed as thekey metric for determining a student’s future potential.However, in 2015 and 2016, three of the UK’s biggestemployers of graduates, Price Waterhouse Coopers, Ernst& Young, and Penguin Random House, challenged thisassumption by dropping the requirement for specificuniversity performance when hiring graduates.1 Theyrealised that university academic performance is not agood indicator of how graduates would perform in reallife, reflecting contemporary higher education methods’(in)effectiveness. Continued...